Say it like Obama the power of speaking with purpose and vision - Leanne, Shelly (McGraw-Hill, 2009)
Obama's outstanding communication skills gave rise to an unprecedented political movement and fueled his success. This book is about the art of persuasion, the power of presentation, and the most effective techniques of communication.